Opioids and Alternatives in Female Chronic Pelvic Pain - Valentine, Lindsey N.; Deimling, Timothy A. (Seminars in Reproductive Medicine, 2018)
Chronic pelvic pain is a complex condition with peripheral and central mechanisms of pain. Successful nonsurgical management typically relies on a multimodal approach, with integration of both pharmacologic and nonpharmacologic interventions. This article reviews nonpharmacologic therapies including pelvic floor physical therapy, dietary modifications, psychotherapy, and acupuncture. These interventions are low risk and should be incorporated into treatment for chronic pelvic pain, as they show promise for successful symptom relief in many overlapping chronic pain conditions. Common nonopioid medications for pelvic are also reviewed, including analgesics, hormone modulating agents, antidepressants, and anticonvulsants. Guidelines for cautious and responsible opioid use are also summarized. While data specific to chronic pelvic pain management remain limited, evidence supporting treatment of other chronic pain conditions is reviewed to help guide management.
Keywords: chronic pelvic pain; opioids; neuropathic pain; complementary method; medical management